Heart Rate Change While Drowsy Driving - Jo, Sang-Ho; Kim, Jin-Myung; Kim, Dong Kyoo (Journal of Korean medical science, 2019)
Heart rate (HR) change during sleepy driving has never been investigated. Healthy volunteers who planned to drive a long distance were recruited and monitored with a 24-hour Holter. Six healthy volunteers were enrolled. Their mean driving time was 297.7 ± 111 minutes. Mean duration of sleepy time while driving was 27 ± 24.5 minutes. Driving HR showed a trend for increment as compared to day time mean HR, from 85 ± 5.6 to 89.8 ± 5.6 beats/min (by 7%) ( = 0.093). Mean HR while sleepy driving significantly decreased to 81.5 ± 9.2 beats/min by 9.3% ± 7.4% ( = 0.046). This pilot study for the first time demonstrated that HR decreased while sleepy driving.